Discover the answers to your questions at Westonci.ca, where experts share their knowledge and insights with you. Discover in-depth answers to your questions from a wide network of experts on our user-friendly Q&A platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
1)
x²-x-6=(x+2)(x-3)
(x+0.5)²-6.25 =[x²+x+0.25]-6.25
=x²+x-6={x-3}{x+2}
2)
x²-x-2=(x+1)(x-2)
=(x-0.5)²-2.25={x²-x+0.25}-2.25
={x²-x-2}={x+1}{x-2}
x²-x-6=(x+2)(x-3)
(x+0.5)²-6.25 =[x²+x+0.25]-6.25
=x²+x-6={x-3}{x+2}
2)
x²-x-2=(x+1)(x-2)
=(x-0.5)²-2.25={x²-x+0.25}-2.25
={x²-x-2}={x+1}{x-2}
We hope our answers were helpful. Return anytime for more information and answers to any other questions you may have. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.